A Comparison of use of Microscopic Examination and PCR for Detection of Entamoeba Histolytica at Wasit Province - Magda A. Ali (Institute of Medico-legal Publications Pvt Ltd, 2021)
A microscopic examination of multiple feces samples of 100 suspected patients with Entamoeba histolyticainfection who suffered from diarrhea was attended to Al-Karamah Teaching hospital at Wasit Province fromJanuary 2020 to March 2020. The feces samples were collected into twoParts; first of direct wet film preparation were done for each sample using normal saline 0.9 % for detectingthe motility of trophozoites and Lugol’s iodine 5% for demonstrating structures and cyst. The 2nd part waskept in freeze (-20C) until used in PCR method .The current study recorded that the overall prevalence rate of Entamoeba histolytica 80(80%) by microscopicexamination and 88(88%) by PCR methods. The prevalence of E. histolytica was higher among families wholive in rural areas 44(55%) than those in urban areas 36(45%) and in males 49(61.3%) more than females31(38.7%). The highest infection rate 37(46.3) was recorded in age group (21-40) years old. The presentstudy was aimed to compare between the microscopic examination and PCR methods in the diagnosis of E.histolytica in human clinical samples.We concluded our results that using PCR technique was more accurate and sensitive (88%) than microscopicexamination method (80%).